War Discourse in Bohdan Tomenchuk’s Poetry: language and memory - Havryliuk, Nadiia (Respectus Philologicus, 2025)
The article analyses the war narrative of the contemporary Ukrainian poet Bohdan Tomenchuk. The object of the analysis is more than three hundred works from the author’s latest collection, each of which contains a war motif. The analysis is based on the works of memory by Maurice Halbwachs, Paul Ricoeur, Friedrich Nietzsche, Michael Basseler, and Dorothee Birke. The methods used are “memory studies” (at the intersection of history and psychology) with an emphasis on the sociological aspect of memory, as well as the hermeneutic method with attention to cognition mediated in symbols. This article aims to explore how B. Tomenchuk records the war through the material and spiritual dimensions. In Bohdan Tomenchuk’s poetry, the material side of war often has a national colour. Weapons (sword, sabre) are correlated with the ancient epochs of Ukrainian history, and elements of protection (body armour) are correlated with national clothing (embroidery). Instead, the spiritual side of the war appeals to the universal experience of war as a wound (shrapnel in the body or torn off pieces, PTSD and mental distress). Ontologically, both physical and mental wounds appear as a symbol of a world fragmented by war, in which the fate of a person and a nation becomes a test of the ability to survive. From the point of view of linguistic representation, we can speak of a minimal number of tropes (similes and metaphors), but symbolization and polysemy in the poet’s works are powerful.